2017
DOI: 10.1007/s00436-017-5716-3
|View full text |Cite
|
Sign up to set email alerts
|

Performance of two immunochromatographic tests for diagnosis of visceral leishmaniasis in patients coinfected with HIV

Abstract: Because of visceral leishmaniasis (VL) urbanization and spreading of the human immunodeficiency virus (HIV) infection to rural areas, coinfection has become more common. Here, we compared the accuracy of Kalazar Detect® (KD), an rK39-based immunochromatographic (IC) test, and OrangeLife® (OL), an rK39 + rK28 IC test, for diagnosing VL in patients coinfected with HIV in an endemic area in Brazil. Seventy-six VL patients and 40 patients with other diseases, of which 31 and 21 patients, respectively, were infecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 40 publications
4
19
0
Order By: Relevance
“…Concerning the different tests applied, aids status in VL patients, and the locality studied, very low sensitivity (25%) was observed in coinfected patients from Natal using Kalazar Detect (POC and IMT) and IT-Leish. These results corroborate those of other authors [32,39] that found low sensitivity in coinfected patients. When considering the localities altogether except for IFA and DAT, all tests had lower sensitivity in coinfected patients.…”
Section: Plos Onesupporting
confidence: 93%
See 2 more Smart Citations
“…Concerning the different tests applied, aids status in VL patients, and the locality studied, very low sensitivity (25%) was observed in coinfected patients from Natal using Kalazar Detect (POC and IMT) and IT-Leish. These results corroborate those of other authors [32,39] that found low sensitivity in coinfected patients. When considering the localities altogether except for IFA and DAT, all tests had lower sensitivity in coinfected patients.…”
Section: Plos Onesupporting
confidence: 93%
“…However, in VL/aids coinfected patients, low sensitivity was achieved. These results corroborate other studies [10,[31][32][33], in which sensitivity ranged from 83-95%, in VL patients, and from 61-67% in HIV/aids coinfected patients and the specificity ranged from 90-100%.…”
Section: Plos Onesupporting
confidence: 92%
See 1 more Smart Citation
“…For example, PCR have been found 88%-96.8% sensitive when conducted with DNA extracted from urine samples [ 14 16 ]. Saliva as diagnostic sample has been reported with 58.6%-82.5% and 83.3% sensitivity in rK39-RDTs and ELISA, respectively [ 17 , 18 ]. rK39-RDTs for sero-diagnostics were also tested with urine samples in several studies and found sensitivities and specificities of 96.40% and 66.2–100%, respectively [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, it has not been used in studies including people from Latin America, and there are few studies discriminating its performance in PLWH. Silva et al [47], using two immunochromatographic tests to detect the antibodies anti-rK39 and anti-rK28, found sensitivities of 67.74 and 61.29%, respectively, in a group with active visceral leishmaniasis and HIV infection, showing poor performance when compared with active visceral leishmaniasis without HIV infection. In our study, in a group of asymptomatic individuals, rK28 ELISA positivity was greater than rK39 ELISA positivity, which can suggest a good perspective of its use in HIVinfected Latin American asymptomatic patients, perhaps as an early marker of Leishmania infection.…”
Section: Discussionmentioning
confidence: 99%